2017
DOI: 10.1186/s12883-017-0960-9
|View full text |Cite
|
Sign up to set email alerts
|

Exercise prescription for patients with multiple sclerosis; potential benefits and practical recommendations

Abstract: BackgroundMultiple sclerosis (MS) can result in significant mental and physical symptoms, specially muscle weakness, abnormal walking mechanics, balance problems, spasticity, fatigue, cognitive impairment and depression. Patients with MS frequently decrease physical activity due to the fear from worsening the symptoms and this can result in reconditioning.Physicians now believe that regular exercise training is a potential solution for limiting the reconditioning process and achieving an optimal level of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
0
27

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(187 citation statements)
references
References 78 publications
(212 reference statements)
5
108
0
27
Order By: Relevance
“…Physical exercise training is often used in the management of MS. Studies have shown that properly prescribed exercise programs can improve modifiable impairments in MS. 5 Exercise is generally safe and well-tolerated. 6 Whole-body cryotherapy (WBC) can support and complement primary treatment and facilitate physical activity. 7 In recent years, the use of WBC has gained recognition as a treatment option.…”
Section: Introductionmentioning
confidence: 99%
“…Physical exercise training is often used in the management of MS. Studies have shown that properly prescribed exercise programs can improve modifiable impairments in MS. 5 Exercise is generally safe and well-tolerated. 6 Whole-body cryotherapy (WBC) can support and complement primary treatment and facilitate physical activity. 7 In recent years, the use of WBC has gained recognition as a treatment option.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate exercise can lead to important improvements in different areas of cardiorespiratory fitness (aerobic fitness), muscle strength, flexibility, balance, fatigue resistance, cognition, quality of life and respiratory function in MS patients (Halabchi, Alizadeh, Sahraian, & Abolhasani, 2017). Some general guidelines exist for exercise in MS patients.…”
Section: Resultsmentioning
confidence: 99%
“…and is rated on a 5-point Likert scale from 0 (Not at all confident) to 4 (Very confident). The items provide two sub-scores "Goal setting" (item 2, 3,4,5,6,7,8,13,14) and "Symptom management" (item 1,9,10,11,12,15). According to the authors [37], the scale is characterized by good item functioning, measurement invariance, and good concurrent validity (positive correlations with positive affect, sense of coherence and coping strategies and negative correlations with depression and negative affect).…”
Section: Methodsmentioning
confidence: 99%
“…Participation in Physical Activity (PA), particularly exercise training, represents the single most effective non-pharmacological approach for managing symptoms and improving the health-related quality of life (HRQoL) of people with MS [4][5][6]. However, people with MS do less PA compared to non-diseased people [7][8][9], but in similar way as other people suffering from a chronic disease [7].…”
Section: Introductionmentioning
confidence: 99%